Pengelolaan Inventaris Berbasis Client - Server sebagai Sistem Monitoring Data Aset - Vivi Kumalasari Subroto; Eni Endaryati; Desi Setyaratna Sari (LPPM Sekolah Tinggi Ilmu Ekonomi - Studi Ekonomi Modern, 2021)
Monitoring is the routine process of collecting data and measuring progress on program objectives. Monitor changes that focus on processes and outputs. Monitoring provides raw data to answer questions, while evaluation is putting the data into use and thus providing added value. Management of equipment at the Research and Development Center of the Department of Religion Semarang is a very important thing to do, because the equipment is one of the company's assets, so that inventory data on these assets must always be maintained in order to provide clear information and facilitate maintenance. The process to ensure that the accuracy and clarity of the information is maintained so that the data recapitulation and data reporting process can run well is monitoring the data. The analytical method used in the development of this system is based on a structured analysis method, where the tools used to model data flow are DFD (Data Flow Diagrams), diagrams for modeling relationships between data are E-R diagrams. This client-server based asset and inventory data monitoring system for the Research and Development Center of the Semarang Department of Religion consists of several access rights, namely the right of access as admin by the LAN & Desktop Support section, and the Manager.